Osteosarcoma of the appendicular skeleton in dogs: consensus and guidelines - Polton, Gerry; Borrego, Juan F.; Clemente-Vicario, Francisco; Clifford, Craig A.; Jagielski, Dariusz; Kessler, Martin; Kobayashi, Tetsuya; Lanore, Didier; Queiroga, Felisbina L.; Rodrigues, Lucas; Rowe, Annika Tranaeus; Vajdovich, Péter; et al. (Frontiers in Veterinary Science, 2025)
Osteosarcoma (OSA) in dogs poses a clinical challenge to veterinary practitioners across the globe. As knowledge evolves, so too do clinical practices. However, there remain uncertainties and controversies. There is value for the veterinary community at large in the generation of a contemporary wide-ranging guideline document. The aim of this project was therefore to assimilate the available published knowledge into a single accessible referenced resource and to provide expert clinical guidance to support professional colleagues as they navigate current OSA challenges and controversies. Primary bone tumors are common in dogs. The history and clinical signs relate to the anatomic site of the tumor. Most canine patients present with a sudden-onset lameness that can appear to improve temporarily in response to analgesia and rest. Most patients do not have detectable metastasis at the time of diagnosis, but most canine patients do develop metastasis within months without appropriate therapy. Surgical resection using wide margins is currently the mainstay of therapy for the local control of the primary tumor. Most commonly, this comprises limb amputation in dogs, but not all dogs are considered good candidates. Anti-metastatic therapy is vital in dogs if surgery is going to offer a good chance of achieving a durable benefit. While there are many limb-sparing and palliative therapy options for dogs with OSA, most have not been shown to achieve superior outcomes compared with amputation and adjuvant chemotherapy. There is a role for radiotherapy in the palliative treatment of OSA. Immunotherapy should be considered a developing treatment modality—multiple immunotherapeutic approaches have yielded positive results in dogs in small experimental studies. It is hoped that this document will serve as a useful resource to practitioners all over the world, to help them better understand this disease and provide the best options for patients to extend quality of life and survival, either within the primary care or referral hospital setting.